USING MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING TECHNOLOGICAL EDUCATION (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the importance of integrating modern pedagogical technologies into the teaching of technological education. It discusses how digital tools, interactive learning platforms, and innovative teaching strategies enhance students’ creativity, critical thinking, and professional skills. The paper emphasizes the role of Smart technologies, STEAM education, project-based learning, and digital simulations in improving the efficiency of the teaching-learning process. It also presents the benefits and challenges of implementing pedagogical innovations in technological education and provides recommendations for teachers and educational institutions.